Search Of Favorite Books As A Visitor Recommendation of The Fmipa Library Using CT-Pro Algorithm - Maryana, Sufiatul; Karlitasari, Lita (Universitas Pakuan, 2018)
The library of Faculty of Mathematics and Natural Science (FMIPA) has a collection of books and other print media, total of 2,678 books with 7237 visitors and 2148 borrowers. The available book search system was very helpful for visitors to find the required books. Especially if the system has features recommended of books. In the provision of book recommendations used one of the data mining techniques, namely association rule mining techniques or excavation of association rules. In the development of this recommendation system, KDD (Knowledge Discovery from Database) model was used. The data used was the transaction history of borrowing book with the category of